An investigation on vibration impact during construction bore piling activity on public receptors in Klang Valley Mass Rapid Transit Serdang project / Muhammad Hafiz Mohd Yatim - Muhammad Hafiz , Mohd Yatim (2018)
Bored piling activity was found to produce low impact energy that could induce vibrational impact towards existing surrounding structures. The vibrational energy could cause disturbances or annoyance to the occupants of surrounding buildings that could affect the occupant’s quality of life. The Klang Valley Mass Rapid Transit (KVMRT) construction in Taman Serdang Raya has fulfilled the criteria of urban development where a high density of buildings were located. This study aims to investigate the vibration impact during KVMRT construction bored piling activity on public receptors within the vicinity of the project site in Taman Serdang Raya. The bored piling activities were monitored by using a vibration level meter in three designated points all across the construction site. The three monitoring points selected were the closest receptor of the bored pile points which is known by its pier’s name, SRN01, SRN10 and SRN22. A baseline study was conducted prior to the bored pile activity. The baseline study was conducted to obtain the existing ambient vibrational condition of the monitoring points. The baseline data is then compared to the Department of Environment (DOE) vibration’s guideline as a benchmarking data to be compared with. Three baseline data were observed to exceed the DOE’s guideline limit which is x axis of SRN01, z-axis of SRN01 and z-axis of SRN10. The baseline data were used as comparison for the bored pile data along with the DOE’s guideline limit. The actual vibration bored pile results have shown two breaches which have exceeded both of the baseline data and DOE’s guideline limit. The exceedances occurred at SRN22 y-axis and SRN22 z-axis. Both of the exceedances were recorded at the same exact time and were contributed by the bored piling activity. Wilcoxon Signed Ranks test conducted has found six out of nine measurement conducted have significant differences between baseline data and bored pile data with two of them achieve a 95% confidence level (p < 0.05) and four have achieved a 99% confidence level (p < 0.01). This study have shown a significant changes of ambient vibration level during bored piling activity was conducted which could provide a basis for vibrational analysis of construction activity.